Humoral and Cellular Immune Response on COVID-19 Patients and Sinovac Vaccine Participants - Brigitte Rina Aninda Sidharta; Mas Aditya Senaputra (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV)-2 is a new SARS-CoV virus. A person who is infected with this virus will induce both humoral and cellular immune responses. Herd immunity can be achieved through vaccination. The purpose of vaccination is the formation of antibodies capable of neutralizing coronavirus against the receptor binding domain. This study aimed to determine the differences between humoral and cellular immune responses between confirmed COVID-19 patients and Sinovac vaccine participants. This observational analytic study with a prospective cohort approach was conducted between March to October 2021. Fifty subjects (25 officers who had received vaccinations for COVID-19 patients and 25 COVID-19 patients treated at the Dr. Moewardi General Hospital) and met the inclusion and exclusion criteria were enrolled. Different tests were carried out to see the difference between the levels of CD8+ T cells and anti-SARS-CoV-2 antibodies in the vaccine group and the COVID-19 patient group. There was no significant difference in humoral immune response (anti-SARS-CoV-2) between the vaccine group and COVID-19 patient group [33.93 (0.4–196.6) U/L vs. 101.28±158.59 U/L; p=0.409], but there was a significant difference in cellular immune response (CD8+) between the vaccine group and COVID-19 patient group [878.52±47368 cells/µL vs. 270.16±213.64 cells/µL; p=0.001]. CD8 assay can be used as a parameter to differentiate the cellular immune response between COVID-19 patients and COVID-19 vaccine recipients.